RI 6153 Treating Beryl-Spodumene Concentrates Containing 10 To 30 Percent Beryl By The Fluosilicate Process ? Summary - R. O. Dannenberg (The National Institute for Occupational Safety and Health (NIOSH), 1963)
Applicability of the fluosilicate sintering process to recovering beryllium from beryl-spodumene concentrate analyzing 1.4 to 3.7 percent BeO (10 to 30 percent beryl) was investigated. The work was one phase of a Bureau of Mines research program undertaken to assess applicability of conventional processes and to devise new procedures for treating various potential beryllium feed materials. Beryllium recovery of about 70 percent in a product of 99-percent BeO grade was achieved in treating 3D-percent beryl concentrate. The process consisted of (1) sintering a briquetted charge of concentrate, soda ash, and sodium fluosilicate for 3 hours at 750° C.; (2) extracting the soluble beryllium by multiple stages of water leaching; (3) adding caustic to the leach solution and boiling to hydrolyze and precipitate crude beryllium hydroxide; (4) dissolving the crude beryllium hydroxide in sulfuric acid and separating the solution from undissolved silica; (5) sulfidizing the acid beryllium solution to precipitate heavy metal impurities; (6) adding ammonia to the clarified sulfate solution to precipitate beryllium hydroxide; and (7) converting the hydroxide to beryllium oxide (beryllia) by calcining at 900° C. About 60 percent more sodium fluoSilicate was required per unit of beryl than is used industrially in treating 10-to 12-percent BeO concentrate (80 to 90 percent beryl). Recovery decreased, and flux requirements increased, when treating concentrates containing less beryl.